Co‐producing knowledge of lesbian, gay, bisexual, trans and intersex (LGBTI) health‐care inequalities via rapid reviews of grey literature in 27 EU Member States. (22nd June 2019) - Sherriff, Nigel; Zeeman, Laetitia; McGlynn, Nick; Pinto, Nuno; Hugendubel, Katrin; Mirandola, Massimo; Gios, Lorenzo; Davis, Ruth; Donisi, Valeria; Farinella, Francesco; Amaddeo, Francesco; Costongs, Caroline; et al.
Abstract: Background: The health inequalities experienced by lesbian, gay, bisexual, trans and intersex (LGBTI) people are well documented with several reviews of global research summarizing key inequalities. These reviews also show how the health‐care needs of LGBTI people are often poorly understood whilst suggesting that targeted initiatives to reduce inequalities should involve LGBTI people. Objectives: To determine what is known about the health‐care inequalities faced by LGBTI people? What are the barriers faced by LGBTI people whilst accessing health care, and health professionals when providing care? What examples of promising practice exist? Design: Rapid reviews of grey literature were co‐produced with LGBTI people in 27 countries followed by a thematic analysis and synthesis across all data sets. The review included grey literature from each country that might not otherwise be accessible due to language barriers. Main results: Rapid reviews showed that LGBTI people faced various inequalities and barriers whilst accessing health care. Where heterosexuality, binary gender and assumed male/female sex characteristics were upheld as the norm, and where LGBTI people differed from these norms, discrimination could result. In consultations where LGBTI people feared discrimination and did not disclose their LGBTI status, health professionals lacked the information required for appropriate assessments. Conclusion: With greater understanding of sexual orientation (LGB people), gender identity (trans people) and sex characteristics (intersex people), combined with access to contemporary knowledge and training, health professionals can work in collaboration with researchers, policymakers and LGBTI people to develop systems that are better attuned to the needs of all service users.